The Influence of Internal Control, Compliance with Accounting Rules and Compatibility of Compensation on the Trend of Accounting Fraud - Wati Rosmawati; Shofia Asry; Ida Harahap (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2023)
The purpose of this study is to gather empirical data on the relationship between internal control, appropriate compensation, and adherence to accounting standards and how those factors affect the tendency of accounting fraud in state-owned companies (BUMN) in the construction industry. The sample of state-owned businesses used in this study (BUMN). Two businesses were selected as samples in this study. Convenience sampling is the foundation of this study. There was a total of 80 respondents in the sample for this study. Several regression analyses approach and a statistical methodology run using the SPSS program are used to test the hypothesis in this study. The findings of this study suggest that internal control, appropriate pay, and adherence to accounting regulations all have an impact on a person's propensity to engage in accounting fraud.